Get live Maths 1-on-1 Classs - Class 6 to 12

Examples

Example 1

Example 2

Example 3

Example 4 Important

Example 5

Example 6 Important You are here

Example 7

Example 8

Example 9

Example 10 Important

Example 11 Important

Example 12

Example 13 Important

Example 14 Important

Example 15

Example 16 Important Deleted for CBSE Board 2023 Exams

Example 17 Deleted for CBSE Board 2023 Exams

Example 18 Important Deleted for CBSE Board 2023 Exams

Example 19 Important Deleted for CBSE Board 2023 Exams

Last updated at March 16, 2023 by Teachoo

Example 6 Champa went to a ‘Sale’ to purchase some pants and skirts. When her friends asked her how many of each she had bought, she answered, “The number of skirts is two less than twice the number of pants purchased. Also, the number of skirts is four less than four times the number of pants purchased”. Help her friends to find how many pants and skirts Champa bought. Let Number of pants purchased by Champa be x & Number of skirts purchased by Champa be y Given that Number of skirts is two less than twice the number of pants purchased (Number of skirts purchased) = 2 × (Number of pants purchased) − 2 y = 2(x) − 2 2x − y = 2 Also, Number of skirts is 4 less than 4 times the number of pants purchased (Number of skirts purchased) = 4 × (Number pants purchased) − 4 y = 4(x) − 4 4x – y = 4 Now, plotting equations 2x − y = 2 ...(1) 4x – y = 4 …(2) For Equation (1) 2x − y = 2 Putting x = 0 2(0) − y = 2 0 − y = 2 y = −2 So, x = 0, y = −2 is a solution i.e. (0, −2) is a solution Putting y = 0 2x − 0 = 2 2x = 2 x = 2/2 x = 1 So, x = 1, y = 0 is a solution i.e. (1, 0) is a solution For Equation (1) 4x − y = 4 Putting x = 0 4(0) − y = 4 0 − y = 4 y = −4 So, x = 0, y = −4 is a solution i.e. (0, −4) is a solution Putting y = 0 4x − 0 = 4 4x = 4 x = 4/4 x = 1 So, x = 1, y = 0 is a solution i.e. (1, 0) is a solution We will plot both equations on the graph Therefore, Solution of the equations is (1, 0) Thus, Number of pants bought by Champa = x = 1 Number of skirts bought by Champa = y = 0